Cancer Epidemiology in China: What We Have Learnt So Far? - Ji, Jianguang; Chen, Tianhui; Shu, Xiaochen; Liu, Hao (Frontiers Media SA, 2020)
After several decades of development, the socialist market economy of China is now the world's second largest economy by nominal GDP. China is also the largest economy by purchasing power parity according to the International Monetary Fund. In tandem with the development of the Chinese economy, China's cancer burden is rising rapidly due to an ageing population and the adoption of unhealthy lifestyle behaviours. According to the data from the National Central Cancer Registry (NCCR) of China, the incidence and mortality of cancer have been increasing rapidly in China. In recent years, cancer has been the leading cause of death among city residents and the second cause of death among rural residents, which has become a stark public health issue in China. According to the NCCR, an estimated 4.29 million new incident cases (12 thousand per day) and 2.81 million death cases (7.5 thousand per day) would occur in 2015 in China. This corresponds to the age-standardized incidence rate (ASIR) of 201.1 per 100,000 and age-standardized mortality rate (ASMR) of 126.9 per 100,000, respectively. Due to the geographical and ethnical disparities in living habits and healthcare level, the cancer spectrum differs between different regions and ethnical groups in China. According to the estimation from IARC, the incidence of nasopharyngeal carcinoma and liver cancer is the world's highest in specific regions of China. The incidence of some cancer types in Chinese urban areas, such as colorectal, prostate, kidney and bladder cancers, is similar to that in developed countries or regions where the incidence of cancer is highly associated with obesity and westernised lifestyles. Nevertheless, the incidence of some common cancer types in rural areas, including oesophageal, stomach, liver and cervical cancers, shares similarity with less developed countries or regions in the world where cancers are associated with chronic infectious agents due to poverty. In addition, the mortality rate is higher in rural areas, which suggests a poorer cancer prognosis due to late diagnosis and/or unsatisfying clinical treatment. The distinct cancer patterns of different regions and/or ethnic groups indicate a need for precise cancer prevention and control plans tailored for different geographical regions and/or ethnic groups. The overarching goal of the proposed Frontiers in Oncology Research Topic is to present current perspectives on cancer epidemiology in Chinese characteristics and provide current knowledge of cancer burden as well as cancer mortality to academic investigators, clinicians and stakeholders from the translational, clinical and public health communities.